Pengaruh Kualitas Pelayanan dan Harga Terhadap Loyalitas Pelanggan di Red Chilies Hotel Solo - Hesti Widyastuti; R. Taufiq Nur Muftiyanto; Indra Hastuti (Jurnal Pemimpin Bisnis Inovatif, 2025)
This research aims to analyze the influence of Service Quality and Price on Customer Loyalty at Red Chilies Hotel Solo. The method used in this research is quantitative with data collected through questionnaires to hotel customers and processed using SPSS 26. The total number of respondents was 99 people. The data analysis techniques applied include validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, coefficient of determination, and F and T tests to determine the relationship between variables. The research results show that Service Quality (X1) and Price (X2) have an effect on Customer Loyalty (Y), proven through a significant T test of more than 0.05 and a calculated r value that is greater than r table 1.661.